Professional phagocytes are recruited for the clearance of obsolete nonprofessional phagocytes in the Drosophila ovary - Chasse, Alexandra Y.; Bandyadka, Shruthi; Wertheimer, Max C.; Serizier, Sandy B.; McCall, Kimberly (Frontiers in Immunology, 2024)
Cell death is an important process in the body, as it occurs throughout every tissue during development, disease, and tissue regeneration. Phagocytes are responsible for clearing away dying cells and are typically characterized as either professional or nonprofessional phagocytes. Professional phagocytes, such as macrophages, are found in nearly every part of the body while nonprofessional phagocytes, such as epithelial cells, are found in every tissue type. However, there are organs that are considered "immune-privileged" as they have little to no immune surveillance and rely on nonprofessional phagocytes to engulf dying cells. These organs are surrounded by barriers to protect the tissue from viruses, bacteria, and perhaps even immune cells. The Drosophila ovary is considered immune-privileged, however the presence of hemocytes, the macrophages of Drosophila, around the ovary suggests they may have a potential function. Here we analyze hemocyte localization and potential functions in response to starvation-induced cell death in the ovary. Hemocytes were found to accumulate in the oviduct in the vicinity of mature eggs and follicle cell debris. Genetic ablation of hemocytes revealed that the presence of hemocytes affects oogenesis and that they phagocytose ovarian cell debris and in their absence fecundity decreases. Unpaired3, an IL-6 like cytokine, was found to recruit hemocytes to the oviduct to clear away obsolete follicle cells. These findings demonstrate a role for hemocytes in the ovary, providing a more thorough understanding of phagocyte communication and cell clearance in a previously thought immune-privileged organ.